Pengaruh Model Pembelajaran Berbasis Proyek Terhadap Kemampuan Kognitif Kelompok B Di RA Ijtihadul Islamiyah - Doyang Besari; Gunawan Gunawan; Nurhasanah Nurhasanah; Filsa Era Sativa (Indonesian Journal of Elementary and Childhood Education, 2025)
This study investigated the impact of a project-based learning (PjBL) model on the cognitive abilities of Group B children at RA Ijtihadul Islamiyah. The specific project involved creating tree figurines from leaves or flowers. This quantitative study employed an experimental approach using a One-Group Pretest-Posttest design. The study's population consisted of Group B children, with a sample size of 19 participants. Data were collected through observation and documentation. The data analysis techniques included evaluating learning implementation, conducting an N-Gain Test, and performing a paired samples t-test. The results showed that the learning implementation achieved a score of 92.85%, categorized as very high. The average N-Gain score was 0.64, indicating that PjBL was moderately effective. Furthermore, the average N-Gain percentage of 64.84% also suggests a fairly effective category in enhancing the cognitive abilities of Group B children. Hypothesis testing using a paired samples t-test revealed a significance value (2-tailed) of 0.00, which is less than 0.05. This led to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha), indicating a significant difference between pretest and posttest results. These findings demonstrate that the project-based learning model had a significant effect on the cognitive abilities of Group B children at RA Ijtihadul Islamiyah. Overall, the project-based learning model is highly suitable for improving children's cognitive abilities.